Kunci Sukses dalam Manajemen Strategi di Era Digital - Mohamad Afrizal Miradji; Bayu Adi; Adheriana Wida; Gunita Gunita; Ella Djamilah Syah; Nabila Mar’atus (Pajak dan Manajemen Keuangan, 2025)
The digital era has brought significant changes in the scope of global business. Demanding companies to adapt quickly and innovatively in managing strategies. This article discusses key factors that determine the success of strategy management amidst digital disruption, including adaptation to technology, data-based decision-making, digital leadership, and the organization's ability to innovate continuously. With a qualitative approach through literature studies and case analysis, this article highlights the importance of digital transformation as the core of modern business strategy. The results of the discussion show that companies that are successful in the digital era are companies that are able to integrate technology into core business processes, build an agile organizational culture, and make data a strategic asset. This article is expected to provide practical insights for business leaders and strategy managers in designing adaptive and competitive policy directions in the midst of the ever-evolving digital era.